Некоторые итоги изучения тектоники угольных месторождений Кузбасса - Коудельный В. Я. Владимир Ярославович; Попов Ю. Н. Юрий Николаевич; Николаев В. В.; Петровский Л. М. (1972, 1972)
Заглавие с титульного листа